Endometriosis Is Characterized by a Distinct Pattern of Histone 3 and Histone 4 Lysine Modifications. (March 2014) - Monteiro, Janice B.; Colón-Díaz, Maricarmen; García, Miosotis; Gutierrez, Sylvia; Colón, Mariano; Seto, Edward; Laboy, Joaquín; Flores, Idhaliz
Background: The histone modification patterns in endometriosis have not been fully characterized. This gap in knowledge results in a poor understanding of the epigenetic mechanisms (and potential therapeutic targets) at play. We aimed to (1) assess global acetylation status of histone 3 (H3) and histone 4 (H4), (2) measure levels of H3 and H4 lysine (K) acetylation and methylation, and (3) to identify histone acetylation patterns in promoter regions of candidate genes in tissues from patients and controls. Methods: Global and K-specific acetylation/methylation levels of histones were measured in 24 lesions, 15 endometrium from patients, and 26 endometrium from controls. Chromatin immunoprecipitation (ChIP)–polymerase chain reaction was used to determine the histone acetylation status of the promoter regions of candidate genes in tissues. Results: The lesions were globally hypoacetylated at H3 (but not H4) compared to eutopic endometrium from controls. Lesions had significantly lower levels of H3K9ac and H4K16ac compared to eutopic endometrium from patients and controls. Tissues from patients were hypermethylated at H3K4, H3K9, and H3K27 compared to endometrium from controls. The ChIP analysis showed hypoacetylation of H3/H4 within promoter regions of candidate genes known to be downregulated in endometriosis (e.g., HOXA10, ESR1, CDH1, and p21 WAF1/Cip1 ) in lesions versus control endometrium. The stereoidogenic factor 1 (SF1) promoter region was enriched for acetylated H3 and H4 in lesions versus control tissues, correlating with its reported high expression in lesions. Conclusions: This study describes the histone code of lesions and endometrium from patients with endometriosis and provides support for a possible role of histone modification in modulation of gene expression in endometriosis.